An investigation of secondary wave-induced intensity modulation in fibre optic gyroscope. Issue 5 (9th March 2017) - Xu, Xiaobin; Zhang, Zhihao; Pan, Xiong; Song, Ningfang; Zhang, Chunxi
Abstract: We propose a double-eigenfrequency-based method to determine the magnitude of the mode-mismatch-induced secondary waves in integrated optic chip in a fibre optic gyroscope (FOG). The experimental results show that the mode-mismatch-induced secondary waves have a magnitude corresponding to power coupling of ~−91.5 dB in the IOC. Based on the obtained secondary waves' magnitude, the effect of secondary wave-induced intensity modulation on the FOG performance is investigated, and the simulation results show that it causes a scale factor error of ~0.01 ppm for a high-precision FOG (bias stability ~0.001 °/h).